Comparative study of interfacial interaction between aromatic and aliphatic functional group in solder wettability - Ismail, Norliza; Ismail, Roslina; Jalar, Azman; Omar, Ghazali; Salleh, Emee Marina; Kamil, Norinsan; Rahman, Irman Abdul (Springer, 2018)
The effect of using different flux on wettability of Sn-Ag-Cu lead free solder were investigated. In this study, solder paste Sn-3.0Ag-0.5Cu (SAC305) was used by introducing two types of no-clean flux with different ingredients. The solders namely as SAC305-A and SAC305-B respectively. Then, the both solder paste manually printed on printed circuit board (PCB) using stencil printing and then reflowed at 260 °C temperature. Wettability of Sn-Ag-Cu solder using different flux was determined by contact angle measurement using Alicona ® IFM software. Results show the SAC305-A solder alloys have a good and better wettability with lower contact angle compared to SAC305-B. Functional groups of both solder flux was identified by FTIR analysis. Meanwhile XPS analysis was performed in characterizing the studied fluxes. It was found that no-clean flux solder with aromatic functional groups showed lower contact angle value and better wettability than aliphatic contained functional groups.